2019
DOI: 10.3390/agriculture9070153
|View full text |Cite
|
Sign up to set email alerts
|

Pongamia pinnata L. Leaves Biochar Increased Growth and Pigments Syntheses in Pisum sativum L. Exposed to Nutritional Stress

Abstract: Pea (Pisum sativum L.) leaf chlorophyll and pigments syntheses are retarded under nutritional stress. Biochar has the potential to regulate soil nutrient supplies and optimize plant nutrient uptakes. We examine the role of Pongamia pinnata L. waste leaf biochar (PLB) in improving vegetative growth and leaf chlorophyll and accessory pigments of pea exposed to nutritional stress. Three PLB application rates (0, 1, and 2%) crossed with half (HF), and full NPK fertilizer (FF) recommended doses were applied to sand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 67 publications
2
12
0
Order By: Relevance
“…Curiously, the concentrations of chlorophyll a, chlorophyll b and total chlorophyll were significantly lower (p < 0.05) for MAPS amended with CWB than for the control soil after 31 days of incubation, but increased non-significantly at the end of the experiment. Hashmi et al [59] reported increments in chlorophyll pigments after the application of Pongamia pinnata L. leaf waste biochar in Pisum sativum L. exposed to nutritional stress. Danish et al [60] also found increments in chlorophyll content in spinach after the application of banana peel waste biochar to a soil contaminated with chromium.…”
Section: Effect Of Biochar Amendments On Plant Germination and Growthmentioning
confidence: 99%
“…Curiously, the concentrations of chlorophyll a, chlorophyll b and total chlorophyll were significantly lower (p < 0.05) for MAPS amended with CWB than for the control soil after 31 days of incubation, but increased non-significantly at the end of the experiment. Hashmi et al [59] reported increments in chlorophyll pigments after the application of Pongamia pinnata L. leaf waste biochar in Pisum sativum L. exposed to nutritional stress. Danish et al [60] also found increments in chlorophyll content in spinach after the application of banana peel waste biochar to a soil contaminated with chromium.…”
Section: Effect Of Biochar Amendments On Plant Germination and Growthmentioning
confidence: 99%
“…These pollutants are taken up by plants and eventually negatively impact many metabolic processes like photosynthesis, respiration, transportation, and nitrogen metabolism [2][3][4][5][6][7][8][9]. These metals can critically affect photosynthesis by damaging the chlorophyll present within plant's chloroplasts [10]. Two basic chlorophylls (chlorophyll a and chlorophyll b) are involved in photosynthesis light reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Biochar contains specific structural sites for the immobilization of heavy metals. The surface adsorption of metals on the carbonized material decreases heavy metals' mobility [10,14,[16][17][18][19][20][21][22]. In this way, food quality is also improved through BC treatment [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Climate changes, environmental pollution, and ever-increasing population growth are major food safety concerns regarding human health [1]. Among abiotic stresses (i.e., drought, salinity, nutrition), heavy metals contamination deteriorate a large agricultural area [2][3][4][5][6][7][8][9]. Soil metal contamination is widespread worldwide in huge land areas, especially in Asian countries, including Pakistan [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%